EVALUATION OF THE EFFICIENCY OF THE PROTECTION ELEMENTS OF THE LOCOMOTIVES AND CARS OF PASSENGER TRAINS ACCIDENTAL COLLISIONS - Naumenko, N. Ye.; Khyzha, I. Yu.; Bohomaz, Ye. H.; Gorobets, D. V. (Science and Transport Progress, 2005)
The estimation of locomotive and car structures dynamic response arising under a train ride into a fixed obstacle or under trains collision was carried out by the computer simulations. Efficiency of use of the combined buffers with additional deformable elements as accident protection devices of locomotive and car structures was shown.